Student Work Sheet Development Based on Cooperative Learning Course Statistics and Probability in the University Pembinaan Masyarakat Indonesia - Rini ST, MT; Yulia Tanjung Tiara (Jurnal Inotera, 2019)
To enhance the learning achievement of each student the lecturer of the course are required to find and implement appropriate teaching methods and effective in each of the learning process so that every learning objectives and teaching can work as expected. Cooperative learning is a form of learning by students to learn and work collaboratively in small groups whose members consist of four to six people with a heterogeneous group structure.